Pengaruh Solvabilitas, Ukuran Perusahaan, Dan Tingkat Suku Bunga Terhadap Return Saham - Andre, Elizabeth Sugiarto Dermawan (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
The purpose of this study is to analyze the effect of solvability, firm size, and interest rate on stock return of manufacture companies listed on Indonesia stock exchange for the period 2015-2017. Sampling method that is used in this research is purposive sampling method and 110 companies are selected as sample. Data processing techniques using multiple regression analysis helped by IBM SPSS Statistics 25 program and Microsoft Excel 2013. The result of this study shows that solvability, firm size, and interest rate are simultaneously have a significant effect on stock return. However, this study shows that partially solvability and firm size don’t have significant effect on stock return but, interest rate has significant effect on stock return